Orthognathic surgical norms for a sample of Saudi adults: Hard tissue measurements - Sahar F. AlBarakati; Laila F. Baidas (Saudi Dental Journal)
Objective: The aim of the study is to establish hard tissue cephalometric norms for orthognathic surgery for a sample of Saudi adults. Materials and methods: Sixty-two lateral cephalometric radiographs for 31 females and 31 males, age range of 22–24 years, were analysed. The mean values of the hard and dental measurements were compared with those of European-American adults using Burstone analysis, as well as comparison between Saudi males and females. Results: Saudi males had an increased cranial base length, the mandible lied more posterior to maxilla, increased mandibular plane angle and backward rotation of the mandible with less prominent chin, shorter maxillary length, and also less proclination of lower incisors compared to those of European Americans. Saudi females had similar cranial base length and shorter maxillary length than European Americans. In both gender; lower anterior and posterior dental heights were smaller when compared with the European-Americans’ values. A significant difference between Saudi males and females was found. Saudi males showed longer cranial base length, larger vertical skeletal proportion, increased dental values, longer maxillary and mandibular length than the female group. Conclusion: This study may be useful in providing racially specific cephalometric norms for diagnosis and treatment planning for orthognathic surgery for a sample of Saudi adults. Keywords: Cephalometric norms, Orthognathic surgery, Saudi adults